1947
DOI: 10.1002/pol.1947.120020604
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of concentrated polymer solutions under periodic stresses

Abstract: Synopsis.Experimental methods for measuring the mechanical properties of concentrated polymer solutions and other viscoelastic systems under periodically varyiny stresses are reviewed. These include direct measurements of stress and strain, measurements of response at resonance frequencies determined by the inertia of the apparatus, propagation of waves in extended media, and measurements of resonance vibrations. The conditions for the suitability of each method are discussed, and equations for the interrelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1952
1952
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The full model (1)(2)(3)(4) reduces to the following closed system of partial differential equations for the remaining unknowns (v x , p, xx , yy ), which are functions of the gap height (y) and time:…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The full model (1)(2)(3)(4) reduces to the following closed system of partial differential equations for the remaining unknowns (v x , p, xx , yy ), which are functions of the gap height (y) and time:…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In [4], a complete solution of this problem is derived resting on the observation that v x and xy decouple into a linear hyperbolic system once yy is negligible, and then the remnant of non-linearity from the upper convective derivative reduces to the solution of (8) with known functions for the velocity and shear stress. The 2 × 2 system (7, 9, satisfying BC1 and BC2) is solved, in the H = ∞ limit by Ferry et al [1][2][3], and generalized to any finite H by the authors [4]:…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest one which shows the same characteristics as our data, is the retarded Maxwell element, first described by Ferry et al [15] and shown in figure 6. It consists of a Maxwell element, ~p G ~s Fig.…”
Section: B Determination Of Maximum Dynamic Viscosity (~1~) and Maximentioning
confidence: 83%
“…This method was extended to the dynamic frequency analysis of linear viscoelastic solutions of polymers. (21)(22) This survey of the literature shows that the penetration test has received moderate attention from researchers. Many semiempirical equations have been proposed to relate measurements (i.e., strength of penetration or velocity) to rheological properties.…”
Section: Introductionmentioning
confidence: 98%